Museums and the Pandemic: Strategies for the Educommunication of Heritage - Quezada-Tello, Laddy (2022)
This article compares the strategies between nine museums in Ecuador, Spain and Peru to address the educommunication activities developed as a result of the 2020 pandemic. Focused on content analysis, the research takes into account the activity of their web pages and the interaction on their social networks. The results show that in Spain informative and informative actions prevailed, while Ecuador and Peru focused on cultural and educational ones. The most relevant contents were oriented to the teaching-learning of heritage, mainly through the development of webinars and online conferences.